.18(6)+0.03x=.09(24+x)

Simple and best practice solution for .18(6)+0.03x=.09(24+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .18(6)+0.03x=.09(24+x) equation:


Simplifying
0.18(6) + 0.03x = 0.09(24 + x)

Multiply 0.18 * 6
1.08 + 0.03x = 0.09(24 + x)
1.08 + 0.03x = (24 * 0.09 + x * 0.09)
1.08 + 0.03x = (2.16 + 0.09x)

Solving
1.08 + 0.03x = 2.16 + 0.09x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.09x' to each side of the equation.
1.08 + 0.03x + -0.09x = 2.16 + 0.09x + -0.09x

Combine like terms: 0.03x + -0.09x = -0.06x
1.08 + -0.06x = 2.16 + 0.09x + -0.09x

Combine like terms: 0.09x + -0.09x = 0.00
1.08 + -0.06x = 2.16 + 0.00
1.08 + -0.06x = 2.16

Add '-1.08' to each side of the equation.
1.08 + -1.08 + -0.06x = 2.16 + -1.08

Combine like terms: 1.08 + -1.08 = 0.00
0.00 + -0.06x = 2.16 + -1.08
-0.06x = 2.16 + -1.08

Combine like terms: 2.16 + -1.08 = 1.08
-0.06x = 1.08

Divide each side by '-0.06'.
x = -18

Simplifying
x = -18

See similar equations:

| X+1.5(x+2)=58 | | 5+3x-7= | | 10n+15n= | | 4[2x-(3-x)+5]=6x-28 | | x/5=4x+1 | | 50x+5897-4312=386135 | | 243=9(10+x) | | 2+u=0 | | 3(3x-2)-5x=x-3 | | 0.10+0.05(52-x)=450 | | (X+2)7=40 | | 6y+1=3x+1 | | 28w-12=16w-30 | | 3r^2-2r-3=0 | | 6x-16=4x+30 | | x^2-5xy+6y^2=0 | | (7x-2)(-5x+6)= | | a^2+14a-99=0 | | -2m-5m=9m-12 | | 7n+1=2n-4 | | -x+19+3x+19=4 | | 50+2x=120-5x | | 24+8=24+2x | | 7y-4=-14 | | u(u^4-13u^2+36)=0 | | 11+m=m-.25 | | x+1=12+3x | | u(u^4-13u^2+63)=0 | | 8a-5a=3a | | 24+2x=24+8 | | 13.4=8.5-x | | -12x+3(x-5)=6-2x |

Equations solver categories